Shaping Claims to Urban Land - van Overbeek, Fons (De Gruyter, 2025)
This book carries forward two entwined projects. One is an empirical concern with hybridization in the shaping of claim-making practices in peri-urban Bukavu. The other concerns operationalizing the concept of 'hybridity' through Foucault's governmentality. The book provides a thought-provoking, step-by-step guidance for those seeking to apply a more ethnographically appropriate reading of governmentality to study governance in the post-colony.